Coimmunoprecipitation on Drosophila cells in culture - Ceriani, Maria Fernanda (2007)
Coimmunoprecipitation (coIP) provides evidence that two or more proteins can be found in the same complex. It can be performed in vitro (employing in vitro transcribed and translated proteins, or proteins expressed in Escherichia coli) or from transfected cells, which assess whether the interaction takes place in a more functional context. This chapter includes a general description and guidelines to carry out coIP in transfected Schneider's cells